Makna Tekstual dan Kontekstual Dialog Pemain Lapor Pak! dalam Youtube “Bercanda Pinggir Jurang” - Kasmanah; Zainal Rafli; Samsi Setiadi (Tarbiya Islamica, 2021)
The purpose of this study was to find and reveal the textual and contextual meanings in the dialogue of the Lapor Pak! players in the YouTube “Bercanda Pinggir Jurang”. This study uses a qualitative approach with text analysis methods and content from YouTube broadcasts. The data collection technique used is the technique of listening, speaking, and taking notes, then narrated and documented. The results of the study indicate that there are textual and contextual meanings in the dialogue of the Lapor Pak! players. The textual meaning in the dialogue includes grammatical and lexical aspects. Grammatical meaning includes references, ellipsis, and conjunctions. While the lexical meaning is in the form of repetition and equivalence. The contextual meaning describes an anecdote text, an interesting short story, containing funny, entertaining, and impressive elements. The components of the text contain interesting messages packaged in humor conveyed by the speakers. The message is in the form of satire aimed at our country, Indonesia. The satire made has the aim of making the related parties who protect corruptors aware and change their attitudes. Between textual and contextual meanings, there is a connection that punishment for corruptors does not need to be viewed subjectively, because the law never looks at who the perpetrator is. This story is expected to make readers aware not to side with the wrong person.